Indicadores de qualidade para sistemas de preparo do solo no transplantio de citros - Vidal, Diego Onofre [UNESP]; Voltarelli, Murilo Aparecido; Da Silva, Rouverson Pereira [UNESP]; Cassia, Marcelo Tufaile [UNESP]; De Oliveira Tavares, Tiago [UNESP] (Lepidus Tecnologia, 2016)
The soil preparation for citrus seedlings planting can affect the longevity, yield, plant health and the quality of the mechanized operations, which must be performed to ensure the future crop management. In this context, this study aimed to evaluate the quality indexes of soil tillage systems during citrus transplanting, through the performance of the operation and the study of times and movements of the mechanized sets. The experiment was conducted in the municipality of Matão - São Paulo, Brazil, in a completely randomized design, with two systems for mechanized soil preparation (conventional and conjugate) to transplant the citrus, with 66 replicates for each treatment. Were evaluated as indicators of quality the wheels slip of the tractor, speed of the mechanized sets, the accuracy of the GPS receiver and a study of time and motion operations, to perform the calculation of the efficiency of the tillage operations of tillage was carried out. All quality indexes for the mechanized sets were unstable, which negatively affects the operations quality. The conjugated tilled system and the liming presented the lowest and the highest speed of the tractor-equipment when compared to others, respectively.
Quality indexes for soil preparation during citrus transplantation
Keywords: Citrus sinensis L.; Control charts; Efficiency of the mechanized; Time and motion study